GERAKAN SAYANG LANSIA PADA MASA PANDEMIK COVID-19 DI DESA KERTAWANGI KABUPATEN BANDUNG BARAT - Susi Kusniasih; Febri Sri Lestari (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
Gerakan Sayang Lansia (GSL) is a government program to make people aware of the role of the elderly so that it is necessary to maintain a balance in the lives of the elderly. There are three factors that can maintain the balance of the elderly in the family in this new normal era, namely biological factors by meeting the physical needs of the elderly by increasing endurance, psychological factors by meeting the mental needs of the elderly to be loved and protected, and socio-cultural factors by providing attitudes and behavior that makes the elderly respected in the family. The target of this regional partnership program is cadres, while the output is increasing the knowledge and skills of cadres. The method used for cadre training begins with a pre-test, providing material about Gerakan Sayang Lansia, mentoring cadres and ending with a post-test. The final result of posyandu cadres, especially in Kertawangi Village, is an increase in the knowledge of health cadres regarding the physical needs of the elderly by increasing endurance through health education about the nutritional needs of the elderly, exercise for the elderly, good hand washing techniques for the elderly, and the use of masks for the elderly; the psychological calm of the elderly; the life of the elderly in social culture through counseling about the importance of attitudes and behaviors that make the elderly respected in the family.